Daya Tarik Wisata Ayodia Oemah Strawberry Di Desa Pengotan, Kabupaten Bangli - Kuntari, Dwi Titi Ayu; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2018)
Ayodia Oemah Strawbe r ry is one of the tourism destinations in Kintamani which is unique and still rarely found in Bali. This agro-tourism-themed tourist venue has a variety of tourist facilities such as a restaurant, racetrack, tree house, spacious yard for outbound, padlock game of love, and the most special is the hydroponic strawberry garden where tourists or visitors can also learn everything about strawberry and how to grow it . T his research will be discussed what kind of tourism attraction are in   Ayodia Oemah Strawbe r ry so that tourists know everything they can do during visit this place . The type of data used in this quantitative research is qualitative and quantitative data, while the data sources are primary data and secondary data. Data collection was done by observation, interview, and literature study. Data was analyzed by using qualitative descriptive data analysis . Result of the research concluded that Ayodia Oemah Strawberry has several complementary points of tourist attraction which are categorized into four terms, as follows attractions, amenities, accessibilities, and ancillary. Overall, Ayodia Oemah Strawberry has complied with the category as one of the tourist destinations in Kintamani. To increase tourist visits, in addition to improving service and range of tourist attractions, the officials should be vigorous in doing promotion through social media.   Keyword : Tourism destination, tourist, attraction , agrotourism, Ayodia Oemah Strawberry